2023
DOI: 10.1039/d2nj04835c
|View full text |Cite
|
Sign up to set email alerts
|

Incorporation of methylene blue into mesoporous silica nanoparticles for singlet oxygen generation

Abstract: Methylene blue is a known photosensitizer able to generate singlet oxygen. The main active species is the monomeric form. However, this dye has tendency to self-aggregate to form dimers and...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
1

Year Published

2023
2023
2025
2025

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 38 publications
0
5
1
Order By: Relevance
“…It is generally acknowledged that both type I (ROS production) and type II (singlet oxygen production) photodynamic reactions are implicated in the tumor cell response to PDT and that the production of these bioactive compounds correlates with successful PDT [ 9 ]. Our results indicate a higher involvement of type I photodynamic reactions compared to type II ones, despite others who have previously shown that both ROS and 1 O 2 are generated by MB [ 41 , 63 ]. However, these results could be explained, considering that several factors may influence the ratio between type I and type II reactions, such as the type of sensitizer, the concentrations of substrate and oxygen, as well as the binding affinity of the sensitizer for the substrate [ 3 ].…”
Section: Discussioncontrasting
confidence: 82%
“…It is generally acknowledged that both type I (ROS production) and type II (singlet oxygen production) photodynamic reactions are implicated in the tumor cell response to PDT and that the production of these bioactive compounds correlates with successful PDT [ 9 ]. Our results indicate a higher involvement of type I photodynamic reactions compared to type II ones, despite others who have previously shown that both ROS and 1 O 2 are generated by MB [ 41 , 63 ]. However, these results could be explained, considering that several factors may influence the ratio between type I and type II reactions, such as the type of sensitizer, the concentrations of substrate and oxygen, as well as the binding affinity of the sensitizer for the substrate [ 3 ].…”
Section: Discussioncontrasting
confidence: 82%
“…MB and also with those of our previous systems based on a stellate type of nanoparticles [32]. We monitored the photobleaching of ADPA (3,3ʹ-(anthracene-9,10-diyl) dipropanoic acid) used as an 1 O2 scavenging probe, using the decrease of its characteristic fluorescence signal as outlined in our previously reported methodology, here described in Section 3.…”
Section: Studies In Watermentioning
confidence: 99%
“…The incorporation of methylene blue (MB) was then performed on aqueous surfactantfree samples. An n MB :n SiO2 molar ratio of 0.00064 was adopted, as it was the highest ratio allowing only negligible MB leaching in our previously reported ST nanoparticles [32]. The incorporation of the photosensitizer was performed in water by stirring the mixture at 25 • C for 1 h. The resulting samples were named MB@u-ST, MB@u-RB, MB@cs-ST/RB, MB@cs-RB/r, and MB@csc-ST/PhS/RB, with u = uniform, cs = core-shell, and csc = coreshell-corona.…”
Section: Incorporation Of Methylene Bluementioning
confidence: 99%
See 1 more Smart Citation
“…For a meaningful comparison with the molecular dyad, PTS was used for the Coulombic dyad at the same concentration as Ruphen (60 µM), resulting in 92% including oxygen, do not yield any product formation. For comparison, traditional organic photocatalysts for singlet oxygen generation, such as rose bengal, methylene blue, and eosin Y, [118][119][120][121][122][123][124][125] were employed in the experiments. However, their performance was notably lower, with yields below 20% following irradiation under our standardized conditions (yellow, pink and pale blue traces in Figure 5 (b)), despite their considerably higher extinction coefficients in the green spectral region compared to the employed ruthenium complexes.…”
Section: Exploiting the Long 3 Pts Lifetime For Photooxygenationsmentioning
confidence: 99%